2021
DOI: 10.3390/ijms22083994
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Novel Transgenic Zebrafish for Studying Adipocyte Development and Metabolic Control

Abstract: Zebrafish have become a popular animal model for studying various biological processes and human diseases. The metabolic pathways and players conserved among zebrafish and mammals facilitate the use of zebrafish to understand the pathological mechanisms underlying various metabolic disorders in humans. Adipocytes play an important role in metabolic homeostasis, and zebrafish adipocytes have been characterized. However, a versatile and reliable zebrafish model for long-term monitoring of adipose tissues has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although co-culture systems in fish remain to be developed, transgenic lines appeared in zebrafish that helped following in vivo adipocyte differentiation processes or adiposity dynamics ( 309 ), through the imaging of adipocyte- or lipid droplet-specific labels (fabp4-EGFP ( 310 );; plin2-TOMATO ( 311 );). Together with the use of a fasting-refeeding experiment (fabp11-EGFP ( 312 );) or a high fat diet ( 311 ) these lines helped reporting on the metabolic regulations that impact on adipose tissues.…”
Section: New Approaches To Specific Analysis Of Tissue Interactionsmentioning
confidence: 99%
“…Although co-culture systems in fish remain to be developed, transgenic lines appeared in zebrafish that helped following in vivo adipocyte differentiation processes or adiposity dynamics ( 309 ), through the imaging of adipocyte- or lipid droplet-specific labels (fabp4-EGFP ( 310 );; plin2-TOMATO ( 311 );). Together with the use of a fasting-refeeding experiment (fabp11-EGFP ( 312 );) or a high fat diet ( 311 ) these lines helped reporting on the metabolic regulations that impact on adipose tissues.…”
Section: New Approaches To Specific Analysis Of Tissue Interactionsmentioning
confidence: 99%
“…Thus, the expression pattern of fabp4a(-2.7):EGFPcaax recapitulates primarily the adipose tissue domain of the endogenous expression pattern of fabp4a. Interestingly, a recent report has shown that the 1.5 kb proximal region of fabp4a directing the expression of cytoplasmic EGFP, also results in an expression pattern restricted to adipose tissue ( Mao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples include visualizing liver, 64 pancreas, 65 and intestinal 66 development, as well as adipose tissue. 67 Fluorescently labeling entire organs or specific cell types facilitates studies of organ development, as labeled cells can be followed over time. Further, in vivo imaging with fluorescent reporter lines makes it possible to investigate cellular processes in real time.…”
Section: Zebrafish As Model Organism For Lipoprotein Researchmentioning
confidence: 99%